Achieving high fuel utilization for microfluidic fuel cell under high flow rate operation. (December 2022) - Li, Li; Ling, Lei; Xie, Yajun; Shan, Shuai; Bei, Shaoyi; Sun, Yanyun; Zheng, Keqing; Xu, Qiang
Highlights: Various optimization strategies are examined and compared in the pursuit of high fuel utilization MFC under high flow rate. Insights into the requirements in geometrical design, electrode material and operation parameter are provided. Useful guidance is given for the future design of flow-through type MFC. Abstract: High fuel utilization is highly desirable in microfluidic fuel cell (MFC) operated under high flow rates. This work provides insight into the requirements in geometrical design, electrode material and operation parameter to realize significantly improved fuel utilization under high flow rate operation for the flow-through type MFC. Detailed parametric analyses are performed and corresponding mechanism investigations reveal that the outer part and downstream region of the electrodes contribute much less than their inner and upstream counterparts in terms of reaction rate owing to the increased ohmic resistance. Consequently, simply increasing the electrode width or length cannot bring satisfactory fuel utilization but only results in a reduced current density. Optimized electrode aspect ratio could realize the simultaneous enhancement of fuel utilization and current density, but the increasing extent is still not satisfying. Compared with the geometrical optimization, developing advanced electrode material is more promising. Increasing the specific surface area of the electrode material is demonstrated more effective than electrochemical activity enhancement since the system suffers a severe mass transfer limitation. Besides, low reactant concentration is found not applicable to the high flow rate system owing to the existence of limiting fuel utilization.